Pengaruh Kepemimpinan Dan Loyalitas Terhadap Kinerja Pegawai Di PT PLN UID Jawa Timur - Renaldi Yayang Gustara; Mei Retno Adiwati (JURNAL ILMIAH EDUNOMIKA, 2021)
This research aims to find out the Influence of Leadership and Loyalty on Employee Performance at PT PLN UID East Java. Data collection methods include check lists, questionnaires, interview guidelines, to cameras for photos or to record images. In this case the method of collecting data through questionnaires by spreading questionnaires to employees of PT PLN UID JATIM. Modeling in the analysis of this study is to use PLS. The results showed that leadership styles that give a very good influence in improving employee performance, as well as employee loyalty have an influence in improving performance. The conclusion of this study is that employees will easily excel and easily improve their performance if the leadership or manager has a good nature, firm and not arbitrary towards employees. Meanwhile, employees who have high loyalty to the company will automatically improve performance directly. Keywords: Influence of Leadership, Loyalty, Employee Performance